Un mouvement contre le jeu d'argent. D'un loisir controversé à un problème public (Vancouver 1994-2004) - Dubuis, Claudia (Editions Alphil Presses universitaires suisses, 2016)
Gambling is now a legitimate sector of the entertainment industry. In the 1990s, opposition emerged in North America but failed to build a social movement on a large scale. This book specifically examines one of these coalitions in Vancouver, Cana-da. The local anti-gambling movement is analyzed as an expression of civic and political engagement. The study focuses specifically on the process of denouncing gambling practices and their conversion into a "public issue." The author analyzes a highly relevant current social debate.